Responsabilité sociale des entreprises : un regard historique à travers les classiques en management stratégique - Sofiane Baba; Rachid Moustaquim; Éric Bégin (VertigO)
Corporate Social Responsibility (CSR) is a fast-growing concern and subject of much debate among both academics and practitioners. However, the vocabulary usually associated with CSR - values, ethics, sustainable development - illustrates a manifest lack of the meaning and scope of CSR. Thus, it appears relevant to analyze the historical development of CSR within the classic management and strategy literature to better understand the fundamentals of today’s debates around CSR. In regards to this research orientation, we analyze the classic literature in management and strategy and identify the historical construction and genealogy of CSR. Our study suggests three main findings. First, the concept of stakeholders and the social responsibility are interwoven and presented as complementary with the basic literature in strategy. Secondly, CSR and profits are not mutually exclusive in principle ; while profits represent a survival necessity, social responsibility relates to institutions moral responsibilities. Third, leaders’ values generally affect business practices in terms of CSR performance.